Factors influencing turnover intention among academics in a private University - Thavapriya, Konasagaram (2019)
In the recent years, higher educational institutions throughout the world including Malaysia have undergone rapid changes, and to meet those changes, the commitment of employees especially the academics is very important. Academics are the backbone of the business in education sector. High turnover rate among academics can hinder the institutions’ abilities to cope with changes and finally affect their performance. This research examines the relationships between salary, training and development, career promotion, working environment and turnover intention among academics in a higher learning institution in Negeri Sembilan. A total of 200 academics was surveyed through a self-administered questionnaire. Statistical Package for Social Science (SPSS) version 21 was employed to perform data analysis of the study. Descriptive, Correlations and Regressions Analyses were performed. The findings of the study revealed that there are significant relationships between salary, training and development, career promotion, work environment and turnover intention. This study however was done in single institution whereby the generalization of the findings could not be made to other higher learning institutions.